Steganographic Methods in Information Protection - Koziel, G. (Штучний інтелект, 2011)
New information protection methods are necessary. Steganography seems to be great opportunity to replace or supplement the cryptographic methods. Steganography gives additional possibilities. It allows to keep in
secret the communication fact and communicating sites personality. A lot of existing methods and the
proposal of a new one are presented in the article. Нові методи захисту інформації є необхідними. Стенографія може замінити або доповнити криптографічні методи. Вона надає нові додаткові можливості і дозволяє зберегти в секреті факти комунікації, а
також деякі аспекти особистої комунікації. У статті описується багато методів і запропонований
новий метод захисту інформації. Новые методы защиты информации являются необходимыми. Стенография может заменить или дополнить криптографические методы. Она предоставляет новые дополнительные возможности и
позволяет сохранить в секрете факты коммуникации, а также некоторые аспекты личной коммуникации.
В статье описывается много методов и предложен новый метод защиты информации.